PRAKSIS POLITIK NABI MUHAMMAD SAW (Sebuah Tinjaun Teori Politik Modern dan Ketatanegaraan) - Fajar Fajar (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2019)
This paper examines the praxis (actions) of the Prophet Muhammad in the phase of Mekka and Madina with the viewpoint of modern political theory. The aim is to provide a theoretical and rational explanation that the actions of the Prophet can not only be seen from a religious viewpoint but can also be seen from a political perspective in measures of political and state theory. One of the Prophet's political actions in the Mecca phase was to build agreements with representatives from the city of Yastrib in the event of the first and second Bai'at Aqabah. The event in the size of political science can be called a social contract, namely building a social agreement to form a joint political entity. So that the event is considered as the first fundamental foundation of the building of the Islamic State. Politically, the Bai'at event can be read like a meeting of two interests in one historical momentum. First, the interests of Muhammad as a messenger of Allah to transmit Islamic teachings to the people of Yastrib. Second, the interests of the Yatsrib community for the presence of a leader who was able to mediate in the social conflict between them - a conflict between the Aus tribe and the never-ending Khazraj tribe. While in the Medina phase, the Prophet's political action was to build a written agreement as a common legal basis that became a guideline for the people of Medina in acting, both socially and politically. This political document is called Shahifah in the original text and later experts call it the Medina constitution, which is the basis for the formation of a state for the Muslim community in Madina.